2009
DOI: 10.1093/imrn/rnp208
|View full text |Cite
|
Sign up to set email alerts
|

The Classification of Exceptional CDQL Webs on Compact Complex Surfaces

Abstract: Codimension one webs are configurations of finitely many codimension one foliations in general position. Much of the classical theory evolved around the concept of abelian relation: a functional relation among the first integrals of the foliations defining the web reminiscent of Abel's addition theorem in classical algebraic geometry. The abelian relations of a given web form a finite dimensional vector space with dimension (the rank of the web) bounded by Castelnuovo number π(n, k) where n is the dimension of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
0
18
0
5
Order By: Relevance
“…Leurs relations abéliennes peuvent toutes être explicitement déterminées en utilisant les résultats de [6]. Les composantes des relations abéliennes non-élémentaires des tissus B k et H l (pour k = 5, 6, 7, 8 et l = 5, 10) sont toutes des intégrales itérées de poids plus petit que 2 (voir [10] pour des détails).…”
Section: Classification Des Tissus Cdql Exceptionnels Sur Le Plan Prounclassified
See 2 more Smart Citations
“…Leurs relations abéliennes peuvent toutes être explicitement déterminées en utilisant les résultats de [6]. Les composantes des relations abéliennes non-élémentaires des tissus B k et H l (pour k = 5, 6, 7, 8 et l = 5, 10) sont toutes des intégrales itérées de poids plus petit que 2 (voir [10] pour des détails).…”
Section: Classification Des Tissus Cdql Exceptionnels Sur Le Plan Prounclassified
“…Les résultats de [10] permettent en fait de classifier les tissus CDQL plats sur P 2 de degré 3 strictement plus grand que 1. Outre les treize exemples sporadiques exceptionnels décris dans le Théorème 3.1, il n'y a que trois autres tels tissus (à équivalence projective près), à savoir…”
Section: Classification Des Tissus Cdql Exceptionnels Sur Le Plan Prounclassified
See 1 more Smart Citation
“…The general philosophy behind our approach (considered for the first time in [7] as far as webs are concerned) is that flatness is characterized by the vanishing of a meromorphic curvature 2-form having poles along the discriminant of the 3web. In [8,5] it is shown that generic invariant components of the discriminant do not produce poles in the curvature.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in [7] the authors introduce the notion of F -barycenter β F (W) of a completely decomposable web W with respect to a foliation F , which was extended in [5] to include the case F is a web. The general statement of Theorem 1 in [5] is that the holomorphy of K(W 2 ⊠ W ′ ) is equivalent to the fact that ∆(W 2 ) be invariant by either W 2 or β W2 (W ′ ).…”
Section: Introductionmentioning
confidence: 99%